Arg753Gln polymorphism of the human Toll-like receptor 2 gene from infection to disease in pediatric tuberculosis - SANCAR, MESUT (ELSEVIER SCIENCE INC, 2011)
The aim of this study is to examine the occurrence of the Arg753Gln polymorphism of the Toll-like receptor 2 (TLR2) gene in Turkish children with pulmonary and/or extrapulmonary tuberculosis (TB) disease compared with that in healthy children with latent TB infection (LTBI) and to assess the risk of progression from LTBI to active TB disease in children. The Arg753Gln polymorphism of the TLR2 gene was studied in 198 TB patients compared with 200 ethnically and age-matched children with LTBI. The culture confirmed TB patients were more frequently Arg753GIn heterozygous [odds ratio (OR) 5.05, 95% confidence interval (95% CI) 2.61-9.76, p = 0.00], and Gln allele frequency was significantly higher in the patient group (13.86% vs 3.5%, OR 4.40, 95% CI 2.34 - 8.30, p = 0.00). We also showed that the frequencies of the heterozygous Arg753GIn genotype and the Gln allele were significantly higher in patients with pulmonary TB alone and in patients with definitive pulmonary plus extrapulmonary TB than in children with LTBI. Our data suggest that the Arg753GIn polymorphism of the TLR-2 gene influences the speed of progression from infection to TB disease in children. Further investigations are needed to clarify whether this polymorphism has a strong impact on susceptibility to TB in children. (C) 2011 American Society for Histocompatibility and Immunogenetics. Published by Elsevier Inc. All rights reserved.
Keywords: Toll-like receptor 2; Single nucleotide polymorphism; Children; Tuberculosis; INTERFERON-GAMMA-RECEPTOR; SINGLE NUCLEOTIDE POLYMORPHISMS; MYCOBACTERIAL INFECTION; SUSCEPTIBILITY; MUTATION; ASSOCIATION; DEFICIENCY; CHILDREN; IMMUNITY; CHAIN